The role of oil in shaping the policy of the United States of America towards the Arabian Gulf region - خالد العلي; ابراهيم علاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Energy security was defined in the 1970s as reducing dependence on imported oil. However, in today's market environment, it is seen as a common interest between producers and consumers. This study examines the efforts of the United States to pursue a long-term oil strategy. In the expansion between production and consumption in the United States, the volatility of oil prices, the potential opening of the oil exploration sector in Saudi Arabia, the Iranian role in developing energy resources from the Caspian Sea basin, and the economic sanctions on Iraq, the main argument is that the prosperity of the American and global economy depends on Availability of Gulf oil in reliable quantities at reasonable prices.